Impact of Baseline Admission Serum Creatinine Level in ST Segment Elevated Myocardial Infarction (STEMI) Patient Undergoing Primary PCI: An Important Predictor of in-hospital and 12-month Survival Outcome - Islam, AHM Waliul; Munwar, Shams; Talukder, Shahabuddin; Reza, AQM; Bhuiyan, Azfar H; Ahmed, Tamzeed; Rahman, Kazi Atiqur; Ali, M Atahar; Alam, Shamsul; Hasan, Mahmud; et al. (Cardiovascular Journal, 2020)
Background: Several studies has shown that impaired renal function might be an important predictor of adverse cardiovascular events in patient with ST elevated myocardial Infarction (STEMI) undergoing primary percutaneous intervention (pPCI). Exact data on clinical impact of baseline or admission serum creatinine level of STEMI patient undergoing pPCI in our patient population not well established. Therefore, we have carried out this non-randomized study to see the effects of S. creatinine level on major adverse cardiovascular outcomes among STEMI patient undergoing pPCI. Methods: Patients were enrolled in this observational non-randomized prospective cohort between November 2017-July 2019, who were presented into our emergency department with acute onset of severe chest pain or angina with ECG evidenced of acute ST elevated myocardial infarction. Total 137 patient (F 12; Male 125) were enrolled in this study. Results: Out of 137 patients, female :12 (8.75%) vs Male: 125 (91.2%). Among, these patient females were more obese (BMI: Female 27.0 ± 2.2 vs male 25.4 ± 4.9) and developed CAD in advance age (Female 59.1 ± 14.5 vs Male 53.4 ± 10.5). Among the 137 patients, 89 (65%) were dyslipidemia, 72 (52.6%) were hypertensive, Diabetic 66(48%), Smoker 70 (51%) and FH positive for CAD were 31 (22.6%). According to the involvement of myocardium infarction, STEMI diagnosis of Anterior MI were 48.9% (n=67) and Inferior MI 51.1% (n=70). An elevated serum creatinine level was defined as creatinine >1.2mg/dl. Based on baseline serum creatinine level, patients were divided into group-A and Group-B. In Group-A. Total 68 patients have S. Creatinine level <1.2 and in Group-B, 69 patients have S. Creatinine level >1.2. Anterior MI were higher in group -B patient than Group-A; Ant MI as 35 (50.4%) vs 31(45.6%), Inf MIL: 34 (49.35) vs 34 (50%), Shock 11 (15.9%) vs 6 (8.8%0, CHB 4 (5.8%) vs 4 (5.9%), Death 12 (17.4%) vs 2 (2.9%) and LVF 5(7.2%) vs 1(1.5%) with 7 days in-hospital stay after primary PCI. Territory wise involvement of vessel in Group-B patient has more involvement of LAD 35 (50.7%) and Group-A has RCA 26(38.2%). Conclusion: In this present study, we found, that in acute STEMI patients, baseline higher serum creatinine level is associated with more AMI related complications and death than in lower serum creatinine level. Thus, we may conclude that baseline admission serum creatinine level may be an important predictor for both in-hospital and 12-month survival outcomes in STEMI patients undergoing pPCI. Cardiovasc. j. 2020; 12(2): 135-142